Modified Banxia Xiexin Decoction Ameliorates Polycystic Ovarian Syndrome With Insulin Resistance by Regulating Intestinal Microbiota - Zhao, Hongyu; Chen, Rufeng; Zheng, Dongxue; Xiong, Feng; Jia, Fan; Liu, Jinyuan; Zhang, Lili; Zhang, Nana; Zhu, Shiqin; Liu, Yongmei; Zhao, Linhua; Liu, Xinmin (Frontiers in Cellular and Infection Microbiology, 2022)
ABSTRACT Objective: To analyze the characteristics of intestinal flora of polycystic ovarian syndrome with insulin resistance (PCOS-IR), and explore the possible mechanism of supplemented Banxia Xiexin Decoction in the treatment of PCOS-IR. Methods: A total of 17 SPF female SD rats, aged 21 days were selected and randomly divided into control group (group Z, n=6), model group (group M, n=6) and treatment group (group A, n=5). PCOS-IR model rats were induced by letrozole combined with high-fat diet. PCOS-IR rats were treated with supplemented Banxia Xiexin Decoction for 2 weeks, then the reproductive, metabolic, inflammatory indices and intestinal microflora of rats in different groups were compared. Results:The PCOS-IR model rats induced by letrozole combined with high-fat diet had the imbalance of intestinal flora, and the enriched flora were mainly Class Coriobacteria, Order Clostridiales and Genus Clostridium_ sensu_ stricto_ 1. Supplemented Banxia Xiexin Decoction can improve intestinal flora imbalance, and can significantly increase the abundance of Phylum Verrucomicrobiota, Phylum Proteobacteria, Genus Akkermansia, and Genus Blautia. Conclusion: Clostridium_sensu_stricto_1 may be the key pathogenic bacteria of PCOS-IR; Supplemented Banxia Xiexin Decoction may treat PCOS-IR by improving intestinal flora imbalance and regulating metabolic disorders.